Business and finance models for increased sustainability and equity of solar-powered irrigation in Pakistan: insights from the private sector - Akbar, Zain M.; Ringler, Claudia; Hafeez, Mohsin (International Water Management Institute, 2024)
During fieldwork in Rahim Yar Khan and Okara districts, Punjab, and on the sidelines of Pakistan Water Week 2024, NEXUS Gains had the opportunity to speak with three solar-powered irrigation system providers to see how the Initiative’s research can support private sector actors and their clientele.